Gender identity disorder / Janet Kalang and Ezzah Syafiqah Seddek - Kalang, Janet; Seddek, Ezzah Syafiqah (2011)
There are billions of people, men and women, throughout this entire world having the difficulty in coping with their real biological gender which often being referred as gender identity disorder or identity problem. This group of individuals is interested to become a person of the opposite gender. According to the Free Dictionary by Farlex, "Gender Identity Disorder is the psychological diagnosis gender identity disorder (GID) is used to describe a male or female that feels a strong identification with the opposite sex and experiences considerable distress because of their actual sex". This problem is often regarded as an abnormality that is hard to be accepted by the society and should never happen in civilized and developed nation like Malaysia. With the balanced and rapid progress in the areas of social, economy and politic, it is believed that the problem of gender identity disorder should not arise as the society are provided with the sufficient knowledge on every aspects of life. However, it cannot be denied that gender confusion is still one of the main social problems that are being discussed frequently by the society, academicians, and political leaders all over the world. As a full time student of UiTM Sarawak, we notice that this phenomenon is also happening here in our campus. Based on our daily observation, we see not only the "soft male" students imitate the female but also the female students who possess the personality of male or in the other familiar term, they are called as "tomboy". Besides that, "Gender identity disorder can affect children, adolescents, and adults. Individuals with gender identity disorder have strong cross-gender identification. Even though this issue is a sensitive matter to be discussed, we have decided to study on it academically. Thus, the main purpose of this study is to fulfill the requirement of our course, Research Paper (PAD340).